Analysis of Recent Growth in Low-Income CIS Countries - Loukoianova, Elena; Unigovskaya, Anna. (Washington, D.C. : International Monetary Fund, 2004)
This paper analyzes factors that determine recent economic growth in the low-income countries of the Commonwealth of Independent States.2 The main findings are as follows: (1) productivity gains in export-oriented sectors and expansion of exports may have become the main sources of growth in five of the seven CIS-7 countries, while in the early years of transition the output recovery was mainly driven by consumption; (2) economic growth has concentrated in agriculture and the raw material sectors, and, thus, is vulnerable to changes in external conditions; and (3) structural reforms matter for growth, which is consistent with previous research on growth in transition countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet